NONENZYMATIC BROWNING KINETIC REACTION AND ASCORBIC ACID DEGREDATION OF HEAT-TREATED ORANGE JUICE DURING STORAGE - Thamer A. Khalil Khalil (Mesopotamia Journal of Agriculture)
The kinetics of ascorbic acid (AA) degradation and nonenzymatic browning (NEB) of heat-treated single strength orange juice (OJ) over a temperature between 70-95 oC for 2-10 min. and stored under opaque condition at 4 and 20 oC for 2 months have been studied. Analysis of kinetic data by measuring absorbance at 420 nm (A420) suggested a zero-order reaction for NEB, while AA degradation followed a first-order reaction. The temperature dependence of NEB and AA degradation were adequately modeled by the Arrhenius equation. Activation energy of NEB and AA degradation as affected by heat-treatment and storage condition followed the same trend. The obtained results indicate that AA degradation can be evaluated by the intensity of brown colour development of OJ.